Evaluasi Kadar Air, Kekerasan dan Sensori Crackers dengan Penambahan Tepung Bekatul Beras Putih dan Tepung Kulit Buah Naga - Hilma Afifah; Sussi Astuti; Novita Herdiana; Esa Ghanim Fadhallah (Jurnal Ilmiah Pangan Halal, 2026)
The utilization of agricultural by-products for raw materials for crackers can be obtained from a combination of wheat flour, white rice bran and dragon fruit peel. Evaluation of water content, hardness and sensory of crackers with the addition of white rice bran flour (TB) and red dragon fruit peel flour (TKN), as well as determining the best comparison level of TB and TKN according to SNI 2973:2018 is the aim of the research. The research was arranged with a single factor and four replications in a Completely Randomized Block Design (RAKL). The single factor was five comparison levels of wheat flour (TT), white rice bran flour (TB), and red dragon fruit peel flour (TKN), namely 100%:0%:0% (K0 /control), 80%:4%:16% (K1), 80%:8%:12% (K2), 80%:12%:8% (K3), and 80%:16%:4% (K4), analyzed by Anara and BNT test 5%. K4 treatment (80% TT: 16% TB: 4% TKN) is the best treatment with a water content of 3.30%, hardness 4.21 N, crispy texture, non-rancid aroma, slightly bitter taste, pleasant color, and a slightly favorable overall acceptance level, acid insoluble ash content of 0.08%, protein 7.38%, crude fiber 4.47%, and dietary fiber 7.03%. The water, protein, and acid insoluble ash content of crackers have met SNI 2973:2018.